Information Literacy, Social Media and Academic Achievement at Higher Education - Kemmouche, Rym (Journal of Human Sciences, 2021)
This study was conducted to investigate the effect of social media usage on information literacy skills and on the academic achievement of second year Master students of English at Frères Mentouri Constantine1 University. It aims at examining the relationship between students’ information literacy competencies and their use of social media. It also attempts to find appropriate methods to measure the study variables: social media usage, information literacy skills and academic achievement. Two questionnaires are used as research tools: one administered to a random sample of 78 students and another one to 16 of their research supervisors. The analysis of the data partly confirms our hypotheses that social media usage would not guarantee the acquisition of the necessary information literacy skills, and that improvement in information literacy performance would enhance students’ academic achievement.